FAMILY RHAGIONIDAE - Santos, Charles Morphy D.; Carmo, Daniel D. D. (Zootaxa, 2016)
The family Rhagionidae is one of the oldest Brachyeran lineages. Its monophyly is still uncertain. There are four rhagionid genera distributed in Neotropical Region but only three species of Chrysopilus are found in Colombia.